Protecting the Civil and Political Rights of Vulnerable Groups in General Elections: A Comparative Study of Indonesia, Türkiye, and Brazil from a Contextualized Islamic Law Perspective - Maharani Nurdin; Muhammad Fauzan; Abdul Azis Nasihuddin; Tedi Sudrajat; Athari Farhani (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2026)
This article examines the legal policies governing the protection of civil and political rights for vulnerable groups in general elections, using Indonesia, Türkiye, and Brazil as comparative case studies. The research focuses on how national legal frameworks ensure equal political participation for persons with disabilities, minority groups, and marginalized communities, while also exploring their alignment with Islamic legal principles. Methodologically, this study employs comparative legal analysis supported by normative–philosophical approaches that contextualize Islamic law (fiqh siyasah) within contemporary democratic practices. The findings show that Indonesia integrates constitutional guarantees with ethical foundations derived from Pancasila and Islamic values, yet implementation gaps remain in accessibility and equal representation. Türkiye operates under a secular legal structure with limited formal references to Islam, but societal norms grounded in Islamic culture influence political inclusion in practice. Brazil provides a contrasting non-Muslim context where strong constitutional mechanisms protect civil and political rights, offering best-practice insights for procedural equality, although challenges persist for racial and indigenous minorities. From an Islamic law perspective, political rights for vulnerable groups are rooted in the principles of justice (al-‘adl), equality (al-musawah), and protection of public interest (maslahah). These principles affirm that safeguarding electoral participation is not only a constitutional mandate but also a moral–religious obligation in Muslim-majority societies. The study concludes that harmonizing positive law with contextualized Islamic values can strengthen legal legitimacy, enhance social justice, and improve inclusive democratic governance in diverse political systems.